2016
DOI: 10.1097/iae.0000000000001017
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Optical Intensity on Optical Coherence Tomography and Visual Outcome in Central Retinal Artery Occlusion

Abstract: Optical intensity ratio on OCT is highly correlated with visual prognosis in central retinal artery occlusion. It may be a potential biomarker of retinal ischemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
28
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 25 publications
3
28
0
Order By: Relevance
“…31 In a later study of 15 patients with CRAO, the same group identified a strong association by Spearman correlation with final BCVA to the optical intensity ratio, a parameter derived by dividing the optical intensity of inner retina by the optical intensity of photoreceptor/RPE layer (r = 0.825, p < 0.001). 32 …”
Section: Ophthalmic Investigationmentioning
confidence: 99%
“…31 In a later study of 15 patients with CRAO, the same group identified a strong association by Spearman correlation with final BCVA to the optical intensity ratio, a parameter derived by dividing the optical intensity of inner retina by the optical intensity of photoreceptor/RPE layer (r = 0.825, p < 0.001). 32 …”
Section: Ophthalmic Investigationmentioning
confidence: 99%
“…An OIR of the inner retina over the RPE calculated from grayscale JPEG images exported from commercial OCT software was found to be associated with a poorer functional outcome in patients with central retinal artery occlusion. 17 Similarly, subretinal fluid OIR obtained by comparing the intensity of a manually segmented region of subretinal fluid with that of the vitreous cavity has been shown to be capable of distinguishing exudation from patients with central serous chorioretinopathy to those with neovascular AMD. 23,24 Browning et al 14 recently used a qualitative analysis and ischemia grading scale to evaluate inner retinal reflectivity in CRVO.…”
Section: Discussionmentioning
confidence: 99%
“…Acute central retinal artery occlusion demonstrates uniform hyperreflectivity of the ganglion cell layer. 17 Paracentral acute middle maculopathy, which is believed to represent focal ischemia at the capillary level, manifests as increased reflectivity at the level of the inner nuclear layer. 18 The degree of reflectivity in the inner retina after acute CRVO varies considerably, but has not been evaluated quantitatively to date as a potential visual prognostic marker.…”
mentioning
confidence: 99%
“…Previously, we have observed increased optical intensity in retinal inner layers during the acute phase of central retinal artery occlusion, which could be a potential biomarker for retinal ischemia. 30,31 Similarly, the increased optical intensity of inner retinal layers in endophthalmitis eyes suggests that inflammation of retinal vessel results in vascular occlusion, subsequently leading to retinal ischemia, and finally atrophy occurs in the retinal inner layers causing irreversible visual impairment.…”
Section: Discussionmentioning
confidence: 99%